ANALYSIS OF THE ROLE OF TOURISM IN POVERTY REDUCTION IN WEST JAVA - Siti Yulia Irani Nugraha; Sukmadi Sukmadi; Hanna Daniati; Irma Citra Resmi; Maksum Suparman (International Journal of Social Science, 2022)
Poverty reduction is not usually at the heart of the tourism agenda. Yet tourism is significant in many poor countries and is already affecting the livelihoods of millions of poor people, positively and negatively. Poverty reduction requires pro-poor growth. Concerted effort is needed to maximize the contribution of tourism to this. Pro-poor tourism (PPT) interventions aim to increase the net benefits for the poor from tourism, and ensure that tourism growth contributes to poverty reduction. PPT is not a specific product or sector of tourism, but an approach. PPT strategies aim to unlock opportunities for the poor whether for economic gain, other livelihood benefits, or participation in decision-making. Pro-poor tourism overlaps with, but is different from, the ‘sustainable tourism agenda. Pro-poor focuses more on countries of the South, not on mainstream destinations in the North. Poverty is the core focus, rather than one element of (mainly environmental) sustainability.